Preparation, Characterization, and in vivo Evaluation of NK4-Conjugated Hydroxycamptothecin-Loaded Liposomes - Zhou, Ting (Int J Nanomedicine, 2020)
PURPOSE: In this study, NK4-conjugated hydroxycamptothecin liposomes (NK4-HCPT-Lips) were prepared with the aim of improving drug targeting to the liver. METHODS: NK4-HCPT-Lips were prepared using the thin-film dispersion method. In vitro antitumor activities were evaluated by MTT assay. HCPT levels in plasma and tissues were determined via high-performance liquid chromatography (HPLC) with camptothecin as the internal standard, and the characteristics, pharmacokinetics, and bio-distribution of NK4-HCPT-Lips were evaluated. RESULTS: The liposomes showed a regular spherical-shaped morphology, and the entrapment efficiency and drug loading capacity reached 82.5 ± 2.4% and 3.01 ± 0.23%, respectively, with a particle size of 155.6 ± 2.6 nm and a zeta potential of −24.8 ± 3.3 mV. Inhibition effect experiments found that NK4-HCPT-Lips had a good inhibition on the HepG2 cells. Pharmacokinetic studies revealed an increase in the area under the curve and mean residence time as well as a decrease in plasma clearance (p < 0.05) of the NK4-HCPT-Lips compared to those of HCPT liposomes and a commercial HCPT injection. Tissue distribution studies showed that NK4-HCPT-Lips were present at high levels in the liver but were cleared from the kidneys. CONCLUSION: These results demonstrate that NK4-HCPT-Lips possess excellent liver-targeting attributes, which could enhance the therapeutic effects of drug treatments for hepatic diseases.